On the long‐term changes of drought over China (1948–2012) from different methods of potential evapotranspiration estimations. (13th March 2018) - Wang, Guojie; Gong, Tiantian; Lu, Jiao; Lou, Dan; Hagan, Daniel Fiifi T.; Chen, Tiexi
Abstract : Assessing the long‐term drought changes is of large interest for understanding the impact of climate change on water resources. Here we have attempted to assess the long‐term drought changes (1948–2012) over China using the self‐calibrating Palmer drought severity index with Penman–Monteith (scPDSIPM ) and Thornthwaite (scPDSITh ) methods for potential evapotranspiration (PET) estimations, respectively, so as to understand the impact of different PET methods on drought assessment. Both scPDSIPM and scPDSITh appear to have drying trends in the humid and transitional climatic regions, which are particularly significant in the north China. Compared to scPDSIPM, the scPDSITh data have resulted in exaggerated drought severity in the north China since 1980s, and such exaggeration is particularly significant for extreme droughts in terms of the occurrences and the intensity. In the dry climatic regions of northwest China, both scPDSIPM and scPDSITh appear to exhibit adequate wetting trends; however, both data have shown drying trends of intensity when drought occurs, indicating there are more extreme dry conditions in the context of generally wetting background. Surprisingly, scPDSIPM is found to result in exaggerated droughts rather than scPDSITh in the northwest China. Abstract : Both scPDSIPM and scPDSITh show significant drying trends in the north China, where the scPDSITh droughts are largely exaggerated. Slightly wetting trends are shown in both scPDSIPM and scPDSITh in the northwest China, where there are however significantly increased droughts. Either the Penman–Monteith or the Thornthwaite method for PET estimations can lead to exaggerated droughts in different regions in the warming climate. Pixel‐wise linear trends for (a) scPDSIPM and (b) scPDSITh, respectively, during 1948–2012.